Alkaloid diversity expansion of a talent fungus Penicillium raistrichii through OSMAC-based cultivation - Zhong, Meijia; Kang, Huihui; Liu, Weizhong; Ma, Liying; Liu, Desheng (Frontiers in Microbiology, 2023)
Introduction Alkaloidal natural products are attractive for their broad spectrum of pharmaceutical bioactivities. In the present work, the highly productive saline soil derived fungus, Penicillium raistrichii, was subjected to the strategy of OSMAC (one strain many compounds) with changes of cultivation status. Then, the work-flow led to the expansion of the alkaloid chemical diversity and subsequently induced the accumulation of four undescribed alkaloids, named raistrimides A–D (1–4), including three β-carbolines (1–3), one 2-quinolinone (4), and one new natural product, 2-quinolinone (5), along with five known alkaloid chemicals (6–10). Methods A set of NMR techniques including 1H, 13C, HSQC and HMBC, along with other spectroscopic data of UV-Vis, IR and HRESIMS, were introduced to assign the plain structures of compounds 1–10. The absolute configuration of 1–3 were elucidated by means of X-ray crystallography or spectroscopic analyses on optical rotation values and experimental electronic circular dichroism (ECD) data. In addition, it was the first report on the confirmation of structures of 6, 7 and 9 by X-ray crystallography data. The micro-broth dilution method was applied to evaluate antimicrobial effect of all compounds towards Staphylococcus aureus, Escherichia coli, and Candida albicans. Results and discussion The results indicated compounds 1, 3 and 4 to be bioactive, which may be potential for further development of anti-antimicrobial agents. The finding in this work implied that OSMAC strategy was a powerful and effective tool for promotion of new chemical entities from P. raistrichii.